Cervical cancer prevention among older women – challenges in screening, diagnostic workup and treatment. (19th June 2021) - Gustafson, Line W.; Petersen, Lone Kjeld; Bor, Pinar; Andersen, Berit; Hammer, Anne
Abstract: Cervical cancer incidence and mortality have declined dramatically after screening for cervical cancer was implemented. Yet, studies have reported high cervical cancer incidence and mortality rates at older age despite low HPV prevalence and incidence of precursor lesions. The underlying reason for these findings remains unclear. However, it is well known that the impact of screening depends not only on the uptake and effectiveness of screening but also on the uptake and effectiveness of diagnostic workup (ie colposcopy), treatment and follow‐up. In older women, sensitivity of screening and performance of colposcopy are impaired due to age‐dependent changes to the cervix. In this commentary, we aimed to discuss challenges in screening and clinical management of older women, and to identify crucial areas of particular interest for future research.